The Legal Force and Effectiveness of the Aarhus Convention in the Polish Legal System - Masternak-Kubiak, Małgorzata (University of Wroclaw. Faculty of Law, Administration & Economics, 2018)
Environmental protection in international law constitutes a complex, multi-faceted task. As civilization advances, a stronger dependency is emerging between phenomena and the comprehensive nature of fundamental human needs, which leads to the continual expansion of the very concept of "environment requiring protection". A very important element in the process of environmental protection is that of the right to information about the environment and the participation of society in taking decisions concerning the environment. Without doubt, from among the many theoretical and practical issues associated with the development of international environmental law, one of particular importance is the question of ensuring the necessary effectiveness of that law in the domestic legal order. The growing international law-making activity in respect of environmental protection renders it necessary to deal now with the need to create conditions for ensuring this law achieves the appropriate level of effectiveness.
Keywords: ochrona środowiska; Konwencja z Aarhus (1998); polskie prawo